2010
DOI: 10.1134/s0006297910030053
|View full text |Cite
|
Sign up to set email alerts
|

Induction of permeability of the inner membrane of yeast mitochondria

Abstract: The current view on apoptosis is given, with a special emphasis placed on apoptosis in yeasts. Induction of a nonspecific permeability transition pore (mPTP) in mammalian and yeast mitochondria is described, particularly in mitochondria from Yarrowia lipolytica and Dipodascus (Endomyces) magnusii yeasts, which are aerobes possessing the fully competent respiratory chain with all three points of energy conservation and well-structured mitochondria. They were examined for their ability to induce an elevated perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Respiring mitochondria maintained their ΔΨ for a long time without any swelling (Kovaleva et al, 2009). Tightly-coupled yeast mitochondria have some advantages over animal mitochondria as they lack a Ca 2+ /P i -dependent pore (Kovaleva et al, 2009(Kovaleva et al, , 2010Trendeleva et al, 2011aTrendeleva et al, , 2011b, a fact facilitating interpretation of the data obtained.…”
Section: Uncoupling Effect Of с 12 Tpp In Yeast Mitochondriamentioning
confidence: 97%
“…Respiring mitochondria maintained their ΔΨ for a long time without any swelling (Kovaleva et al, 2009). Tightly-coupled yeast mitochondria have some advantages over animal mitochondria as they lack a Ca 2+ /P i -dependent pore (Kovaleva et al, 2009(Kovaleva et al, , 2010Trendeleva et al, 2011aTrendeleva et al, , 2011b, a fact facilitating interpretation of the data obtained.…”
Section: Uncoupling Effect Of с 12 Tpp In Yeast Mitochondriamentioning
confidence: 97%
“…Although the configuration of pores formed by ALM Q7K analogue differed from that observed previously for ALM [61], regarding the transmembrane orientations of peptides, the helicity of ALM Q7K was found to be comparable to that calculated for ALM. In a further study, MD simulations were carried out by [68] reported that ALM induced large-amplitude swelling of mitochondria and the formation of 1 nm channels in mitochondrial membranes permeable to divalent cations and low-molecular weight compounds. Kuharczyk et al…”
Section: Theoretical Studies Zhan and Lazaridismentioning
confidence: 99%
“…In contrast, cyclosporin A failed to afford protection from the PTP in wheat ( Triticum aestivum L.) mitochondria, even in the presence of dithioerythritol [14]. Furthermore, no Ca 2+ ‐induced PTP could be found in mitochondria from the yeast Endomyces magnusii [15–17]. Likewise, no Ca 2+ ‐induced PTP could be found in mitochondria from embryos of the crustacean A. franciscana [18].…”
Section: Introductionmentioning
confidence: 99%